Mu’jam al-Musthalahat fi Kitabati al-Maqalah al-Ilmiyyah ‘Inda Sah Khalid Nasution min an Nadzariyyah al-Mu’jamiyyah - Fadhlin Ghafur Maspar; Nida Ul-Haqq; Miftahul Huda; Slamet Daroini (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2021)
Dictionaries play a fundamental role in language learning by assisting teachers, students, and researchers in understanding the meanings and uses of words and specialized terminology. Among the various types of dictionaries, glossaries of scientific terms are particularly important for novice learners because they facilitate the comprehension of technical vocabulary frequently encountered in academic writing. This study aims to evaluate the Glossary of Scientific Article Writing Terms compiled by Dr. Sah Khaled Nasution by examining its compliance with accepted principles of lexicographic compilation and identifying its potential applications in academic contexts. This research employed a qualitative approach using the documentary research method. Data were collected through document analysis, with the glossary serving as the primary source of data. The analysis focused on the dictionary's structure, content organization, presentation, and conformity with established lexicographic standards. The findings indicate that the glossary generally meets the essential criteria of a well-constructed specialized dictionary. In terms of design, it provides a clear introduction, states its objectives, includes explanatory information, and presents definitions systematically. Regarding content quality, the glossary demonstrates coherence, conciseness, objectivity, and a focused presentation of scientific terminology, making it suitable as a reference for academic writing. Overall, the glossary can be considered a useful and reliable lexicographic resource for students and researchers. However, the study also identifies several limitations, particularly the absence of etymological information and the lack of comprehensive explanations regarding the origins and broader usage of the listed terms. These shortcomings suggest the need for further development to enhance the glossary's value as a comprehensive academic reference.